A Comparative Study on the Photocatalytic Activity of Eucalyptus Leaf Assisted Green Synthesized ZnO and Chemically Synthesized ZnO towards the Degradation of Malachite Green Dye. Issue 205 (12th February 2020) - Devi, Sh. Anju; Singh, K. Jugeshwar; Devi, K. Nomita
Abstract: The photocatalytic activities of ZnO nanoparticles, synthesized by two methods, towards the degradation of Malachite green (MG) dye were studied and compared. Green synthesized ZnO nanoparticle was observed to be more effective in photodegradation and the effect of operating parameters such as catalyst loading, initial dye concentration and pH was investigated. Optimum condition was observed at catalyst load 0.24 g/L, initial dye concentration 20 ppm and pH nine which degrades 90% of the dye under 1 h of irradiation. X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Energy Dispersive X-ray spectroscopy (EDX), UV-Vis spectroscopy and Fourier Transform Infrared spectroscopy(FTIR) were employed as characterization techniques for the samples.